Relationship between farm structure and animal feed in unstable non-acid milk occurrence in Planalto Norte of Santa Catarina Relação da infraestrutura da propriedade e alimentação dos animais na ocorrência de leite instável não Ácido no planalto Norte de Santa Catarina - Voges J.G.* (2018)
© 2018 Universidade Federal de Goias. All Rights Reserved.The alcohol test is largely used in the dairy reception platform in order to verify raw milk stability. Milk that is not stable in the test and does not present high acidity is defined as unstable non-acid milk (UNAM). Its occurrence has a multifactorial characteristic and may be related to inadequate nutritional management. This study aimed to evaluate the influence of farm structure and animal feed on the occurrence of UNAM. The farm structure was characterized by means of a semi-structured questionnaire guide. Milk composition of the farms, resistance to alcohol test, titratable acidity and pH were analyzed. UNAM samples were those that precipitated at alcohol concentration less than or equal to 72%, with normal acidity and pH. Neutral detergent fiber was determined in the feed collected. Data were evaluated using factor and cluster analysis by using SAS statistical package. The use of roughages and concentrated food supplements with consequent improvement of animal productivity and higher lactose content in milk were associated with lower occurrence of UNAM under the studied conditions. The occurrence of UNAM had little relation with the farm structure and with the season of the year.